2018
DOI: 10.1002/ajp.22935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vitamin D metabolites in wild and captive baboons

Abstract: Vitamin D adequacy is essential for multiple physiologic processes. With limited exposure to sunlight for vitamin D3 synthesis, captive primates are supplemented with vitamin D3 (cholecalciferol). Vitamin D metabolite data from wild primates living indigenously could suggest optimum levels. The purpose of this study was to: 1) to explore whether baboons, a speciose genus whose members have significant exposed skin, coat color variation and wide geographical distribution, mirrors the skin pigmentation-vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, it is appropriate to recognize that small concentrations of 25(OH)D2 are present in human population studies [ 158 ]. These small concentrations may reflect food sources, as comparable levels are observed in free ranging baboons [ 159 ]. Additionally, much higher 25(OH)D2 levels may be observed clinically as ergocalciferol is widely available and highly prescribed in some countries.…”
Section: Variability In the Form Of Vd That Is Needed For Specific Situationsmentioning
confidence: 95%
“…However, it is appropriate to recognize that small concentrations of 25(OH)D2 are present in human population studies [ 158 ]. These small concentrations may reflect food sources, as comparable levels are observed in free ranging baboons [ 159 ]. Additionally, much higher 25(OH)D2 levels may be observed clinically as ergocalciferol is widely available and highly prescribed in some countries.…”
Section: Variability In the Form Of Vd That Is Needed For Specific Situationsmentioning
confidence: 95%
“…An LC–MS/MS panel was used to measure vitamin D 3 metabolites (Ziegler et al, 2018). As the serum level of vitamin D 3 metabolites are on average higher in the common marmoset than in the Old World monkeys, the volume used for the extraction and analyses was reduced to 50 µl.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, striking levels of variation in vitamin D status within species was detected even in laboratory primates that were subject to controlled diet and UV exposure [ 97 ]. Additionally, vitamin D status has been demonstrated to be lower in darker skinned baboons than in those with lighter skin, however there were no differences in downstream metabolites suggesting that downstream conversion is under strong regulatory control [ 98 ].…”
Section: Vitamin D Metabolism In Veterinary Speciesmentioning
confidence: 99%
“…No reference range exists for 3-epi-25(OH)D3 in humans, therefore data from a systemic review which reported ranges from several studies was used (see Bailey et al (2013) [ 79 ]). The number of studies included to provide data for each of the veterinary species are as follows: ( A ) dogs n = 8 [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], cats n = 1 [ 85 ], horses n = 1 [ 88 ], sheep n = 4 [ 30 , 89 , 90 , 91 ], cattle n = 2 [ 92 , 93 ], pigs n = 1 [ 94 ], poultry n = 2 [ 95 , 96 ] and nonhuman primates n = 2 [ 97 , 98 ]; ( B ) dogs n = 2 [ 81 , 85 ] and cats n = 1 [ 85 ]; and C . dogs n = 1 [ 83 ].…”
Section: Figurementioning
confidence: 99%